2022
DOI: 10.1002/jsfa.12243
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed peptide inhibits HepG2 cell proliferation by regulating the mitochondrial and P53 signaling pathways

Abstract: Background Rapeseed peptide, extracted from rapeseed protein, is known to have a variety of biological activities. In this study, the anti‐proliferation effect and molecular mechanism of rapeseed peptide on HepG2 cells were investigated. Results In vitro anticancer experiments showed that the rapeseed peptide NDGNQPL could inhibit HepG2 cell proliferation in a concentration‐dependent manner [half maximal inhibitory concentration (IC50), 1.56 mmol L−1). HepG2 cells were induced by NDGNQPL at a 0.5 mmol L−1 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Antitumor drugs can cause cell cycle arrest and death via activating signalling pathways 85 , 86 . Cell growth in various cell cycle phases is measured by flow cytometry 87 , 88 .…”
Section: Resultsmentioning
confidence: 99%
“…Antitumor drugs can cause cell cycle arrest and death via activating signalling pathways 85 , 86 . Cell growth in various cell cycle phases is measured by flow cytometry 87 , 88 .…”
Section: Resultsmentioning
confidence: 99%
“…Preparations of corn peptides were found to exert growth-restraining, cell cycle-damaging, and apoptosis-promoting effects, and the “in vitro” results were corroborated by evidence of “in vivo” inhibition of hepatocellular carcinoma [ 62 ]. Apoptosis was also triggered by peptides isolated from mung beans and rapeseed protein hydrolysates [ 63 , 64 ]. To our knowledge, the results reported herein, which add themselves to this short list, represent the first evidence of small linear anti-cancer peptides, both natural and modified, derived from a marine plant species.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, Ma et al's study showed that HepG2 cells were induced by rapeseed peptides and exhibited a P53-mediated cell cycle arrest in G0/G1 phase. 38 This suggests that SPs most likely inhibit the proliferation of HepG2 cells by downregulating P53 expression and thereby regulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%